BIOIMPEDANCE MARKERS AND TUBERCULOSIS OUTCOME AMONG HIV-INFECTED PATIENTS - Montalvo, Raúl; Bernabe-Ortiz, Antonio; Kirwan, Daniela E.; Gilman, Robert H. (African Journal of Infectious Diseases (AJID), 2018)
Background: The changes in body composition markers (weight, fat mass, lean mass, and BMI) over time can be associated with TB treatment outcome among HIV-infected patients. The aim of this study was to investigate whether changes in fat mass and lean mass were associated with the treatment response among patients with HIV infection and pulmonary tuberculosis. Materials and Methods: This was a prospective cohort study. Data from HIV-infected patients commencing TB therapy were analyzed. This included body weight measurement using bioimpedance equipment at baseline, one month, and two months after starting TB treatment. Results: The study was conducted in 125 patients, 17 patients (13.6%) died during treatment, of which 5 died during the first month of treatment, 4 during the second month and 8 after the second month. The group of patients with good response, increased their weight by 1.3 kg (p <0.001) at the end of the first month of TB treatment and 2.6 kg in the second month (p <0.001), and body fat increase was 1.2 Kg (p <0.001) and 2.3 kg (p <0.001), the first and second month respectively. The group of patients who died had lost 2.1 kg fat mass after the first month (p <0.001) and 3.7 kg in the second month (p <0.001). Conclusions: Our results show that the weight change during TB treatment (increased fat mass) helps us predict therapeutic response. Weight loss during the first month of starting therapy should be evaluated thoroughly to identify the probable cause of treatment failure.